Universal Digital Model of a Child’s Pelvis - Suvorov, V.L.; Filipchuk, V.V.; Melnyk, M.V. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Developmental dysplasia of the hip (DDH) is a common hip joint pathology in pediatric orthopedist’s practice. Untreated DDH or residual acetabular dysplasia in walking patients usually requires surgery (pelvic osteotomy is one of the surgical options). During pelvic osteotomies, plastic changes take place in so-called ’hinge points’. These hinge points are described in the literature; however, there are some contradictions regarding the classical locations of these hinge points. Objective: to develop a digital pelvic model that can be used for various pelvic osteotomies modeling. Materials and Methods. Pelvic CT scans of a 6-year-old child were obtained, and a virtual model of pelvic bones was created. Pemberton pelvic osteotomy was simulated, material properties were assigned, and pelvic ligaments were added. Simulation of the Pemberton osteotomy was performed, and biomechanical changes during this intervention were assessed. Results. The digital pelvic model of a 6-year-old child was created, Pemberton pelvic osteotomy was simulated, and biomechanical changes during this surgery were evaluated. It was found that there is no single hinge point during this surgery (as believed previously); the main stress generation took place in triradiate cartilage anterior and posterior arms. Pelvic ligaments’ role during Pemberton pelvic osteotomy was assessed (sacrospinous and sacrotuberous ligaments were the main constraints during the lower iliac fragment movement). Also, the possibility of simultaneous bilateral application of Pemberton pelvic osteotomy or its combination with other pelvic osteotomies in 6 years old patients was biomechanically justified. Conclusions. The development of a digital pelvic model with subsequent pelvic osteotomies modeling according to the method described in this article allows to evaluate biomechanical changes during these osteotomies.